Command Detection and Classification in Tongue Drive Assistive Technology - Sadeghian, Elnaz Banan (2011)
Tongue Drive System (TDS) is a new assistive technology that enables individuals with severe disabilities such as those with spinal cord injury (SCI) to regain environmental control using their tongue motion. We have developed a new sensor signal processing (SSP) algorithm which uses four 3-axial magneto-resistive sensor outputs to accurately detect and classify between seven different user-control commands in stationary as well as mobile conditions. The new algorithm employs a two-stage classification method with a combination of 9 classifiers to discriminate between 4 commands on the left or right side of the oral cavity (one neutral command shared on both sides). Evaluation of the new SSP algorithm on five able-bodied subjects resulted in true positive rates in the range of 70–99% with corresponding false positive rates in the range of 5–7%, showing a notable improvement in the resulted true-false (TF) differences when compared to the previous algorithm.